Pengaruh Variasi Suhu dan Durasi Pengepresan pada Kualitas Lemak Kakao - Hasanah, Tyas Titi Nur; Bimantio, Mohammad Prasanto; Ulfah, Maria (Jurnal Agro Industri Perkebunan, 2024)
This research aims to explore the impact of temperature and duration of cocoa pressing on the properties of the cocoa butter produced, as well as the organoleptic preferences of the panelists. The pressing process uses a hydraulic press method for cocoa paste. This research design was carried out using two factors, namely pressing temperature with three levels: 50°C, 70°C, and 90°C, and pressing duration with three levels: 30, 40, and 50 minutes. The cocoa butter produced was analyzed for yield, free fatty acid content, water content, saponification value, iodine value, peroxide value, and antioxidant activity. The results showed that pressing temperature significantly influenced yield, water content, free fatty acid content, saponification value, iodine value, peroxide value, and antioxidant activity. Meanwhile, the duration of pressing only affects the yield, water content, saponification value, iodine value, and peroxide value. The cocoa butter produced can meet SNI standards. It has high antioxidant activity, which is obtained under operating conditions at a temperature of 50°C for 30 minutes, even though it produces the lowest yield. This research shows that lower pressing temperatures and duration can produce good quality cocoa butter, which panelists accept without changing the aroma, appearance, and original composition, even though the resulting yield is lower.